Evaluation of Historical Building Economic Value To Improve Company Revenue With Value Engineering Method - Suwandari, Yunita Dian; Mirnayani, Mirnayani (Semarang State University, 2021)
Abstract: Historical buildings have high historical, cultural, and architectural values. This research aims to provide an overview of the economic benefits for building owners when utilizing the building. Case studies, the qualitative methods and Value Engineering were used in this research. This study identified three building functions to add economic value and are feasible in terms of investment value. The buildings are a budget hotel, restaurant/cafeteria, and co Ã¢â‚¬â€œ working space. IRR value for budget hotels is 14.29%; the NPV value is IDR 58,375,939,253; 14 years payback; the distribution of the financing scheme 30% landowners and 70% investors; 30-year concession. Restaurant / cafÃƒÂ© and co Ã¢â‚¬â€œ working space; the value of IRR is 12.47%; the value of NPV is IDR 4,727,841,299.58; Payback 8 years. This research is useful for historic building owners, government, and academics to utilize their assets to have economic value. Ã‚Â